Fall-Recovery Technique as Technology in Dancer’s Body - Kiki Rahmatika (IJCAS (International Journal of Creative and Arts Studies), 2018)
the human body is a tool that capable of understanding and then reveal various problems that exist in the social life. Body as tool means a body that has a technique or as technology that is able to express the problem. if the body has been positioned as a tool, of course the tool must have a technique that has been honed its ability. For example fall-recovery’s technique which is discovered by dorris Humphrey. then to get to the technique, the body must get treatment, conditioning and emphasis through strict discipline. ultimately the techniques that make the body into technology will be constructed through body behavior which is doing by long exercises and method from the right technique.